2007
DOI: 10.1007/s11011-007-9060-7
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of hepatic encephalopathy

Abstract: Current recommendations for the treatment of hepatic encephalopathy are based, to a large extent, on open or uncontrolled trials, undertaken in very small numbers of patients. In consequence, there is ongoing discussion as to whether the classical approach to the treatment of this condition, which aims at reducing ammonia production and absorption using either non-absorbable disaccharides and/or antibiotics, should be revisited, modified or even abandoned. Pros and cons of present therapeutic strategies and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 68 publications
0
52
0
1
Order By: Relevance
“…However, there are several drugs being examined in research and clinical trials that could benefit patients with HE. Most of them tend to reduce the production and absorption of ammonia from the colon (Bass, 2007;Morgan et al, 2007). Furthermore, non-absorbable disaccharides inhibit bacterial ammonia production in the colon and retard ammonia as non-diffusable ammonium in the intestinal colon (Cammà et al, 1993).…”
Section: Therapeutic Means In Hepatic Encephalopathymentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are several drugs being examined in research and clinical trials that could benefit patients with HE. Most of them tend to reduce the production and absorption of ammonia from the colon (Bass, 2007;Morgan et al, 2007). Furthermore, non-absorbable disaccharides inhibit bacterial ammonia production in the colon and retard ammonia as non-diffusable ammonium in the intestinal colon (Cammà et al, 1993).…”
Section: Therapeutic Means In Hepatic Encephalopathymentioning
confidence: 99%
“…Phenylacetate conjugates with glutamine, a major detoxification product of ammonia, to form phenylacetylglutamine, which is excreted by the kidney. Sodium benzoate, on the other hand, reduces ammonia levels in blood because it is metabolized to hippurate by conjugation with glycine, which is rapidly excreted by the kidney (Morgan et al, 2007).…”
Section: Therapeutic Means In Hepatic Encephalopathymentioning
confidence: 99%
“…Given the primary role of ammonia neurotoxicity in the pathogenesis of HE, management strategies focus on reduction and/or elimination of ammonia, in addition to treatment of precipitating factors, when identi fi ed [ 72,73 ] . The most commonly administered treatment for HE is lactulose, which is a nonabsorbable disaccharide that remains undigested until it reaches the colon.…”
Section: Treatmentmentioning
confidence: 99%
“…9 Some alterations of patients with cirrhosis may be associated with zinc deficiency: alopecia, wound healing disorders, lack of appetite, hypogeusia, gonadal growth retardation, 10 and it is also associated with hepatic encephalopathy. 11,12 A study with adult patients with decompensated cirrhosis found that these patients have plasma zinc concentrations significantly lower than patients with compensated disease, and that zinc concentrations are negatively associated with fasting ammonia concentrations. 13 Because of its role during the growth period and for immunocompetence, we evaluated and compared zinc concentrations in children and adolescents with liver disease.…”
mentioning
confidence: 99%